Insert sheet, transfer film, and method for manufacturing insert sheet
Patent Information
- Application Number
- JP2024135096
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-08-14
- Filing Date
- 2024-08-13
- Publication Date
- 2025-02-27
AI Technical Summary
【0100】 VOC試験について分かるように、水性インサートシートはより良い値に達する。VOC試験の値が低いほど、インサートシートは良好で環境に無害である。更に、臭気試験に対しても、本発明による水性インサートシートは、溶媒系層を有する従来型インサートシートよりも良好な性能を有する。
Smart Images

Figure 2025027464000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an insert sheet, a transfer film, and a method for producing an insert sheet. [Background technology]
[0002] The insert molding process is usually used for the production of decorated molded parts, especially in the automotive sector. For this, plastic substrates, especially in flat two-dimensional form, are decorated with a transfer ply of transfer film. These decorated substrates are usually called inserts. After decoration, such inserts are formed, especially deep drawn, into three- or 2.5-dimensional forms and inserted into the mould of an injection moulding machine. To provide the decorated moulded part, the inserts are back-injected with a plastic compound. Compared to other decoration processes, such as spray painting or in-mold decoration (IMD), the insert molding process is more stable and offers much more decorative design options. The insert molding process combines in-mold injection and decoration in one operation. It therefore reduces labour, energy and costs. The main advantage of the insert molding process is that it is suitable for deeply drawn, especially deep drawn, three- or 2.5-dimensional parts and can meet various design requirements.
[0003] However, solvent-based coatings are conventionally used for the layers of the transfer ply of the transfer film used to decorate the insert sheet. These are, for example, solvent-based topcoat layers, solvent-based ink layers and solvent-based adhesive layers. Such solvent-based lacquers contain a large number of different solvents. During printing, almost all of the solvent evaporates. However, the residual solvent in the transfer film also generates a high VOC (= volatile organic compounds) content in the final decorated molded part. Such volatile organic compounds are harmful to the human body as well as to the environment. Conventionally, due to the use of solvent-based lacquers even in the manufacturing process of the transfer film, especially the insert sheet, numerous safety measures have to be met to avoid air pollution. Such safety measures are costly. Summary of the Invention [Problem to be solved by the invention]
[0004] Therefore, it is an object of the present invention to identify an insert sheet and transfer film that are environmentally harmless, as well as a method for producing the insert sheet. [Means for solving the problem]
[0005] This object is achieved by an insert sheet comprising a substrate and a transfer ply of a transfer film applied to the substrate, the transfer ply comprising at least one water-based adhesive layer, at least one water-based color layer, and a water-based topcoat layer, in particular arranged on the substrate in the following order:
[0006] This object is further achieved by a transfer film for decorating an insert sheet, in particular as described in any one of claims 1 to 8, comprising a carrier layer and a transfer ply, the transfer ply comprising an aqueous topcoat layer, at least one aqueous color layer and an aqueous adhesive layer, in particular arranged on the carrier layer in the following order:
[0007] Furthermore, the object is to provide a method for producing an insert sheet, preferably according to claims 1 to 8, which comprises a substrate and a transfer ply of a transfer film, in particular according to claims 9 to 15, applied to the substrate, providing a carrier layer; applying, by printing, in particular in the following order, an aqueous topcoat layer, at least one aqueous color layer and an aqueous adhesive layer onto the surface of a carrier layer to provide a transfer film; A step of providing a base material; heat laminating a transfer ply of a transfer film onto a surface of a substrate; Including, In particular, this is achieved by a method characterized in that the water-based adhesive layer is directly adjacent to the surface of the substrate.
[0008] The present invention makes it possible to reduce or completely avoid the amount of environmentally harmful solvents in the manufacturing process of the insert sheet and in the insert sheet itself. The use of water-based lacquers for the top coat layer and / or the color layer and / or the adhesive layer and / or the tie coat layer makes it possible to produce environmentally harmless insert sheets and / or decorated molded parts, particularly for the automotive sector, while these decorated molded parts and / or insert sheets have almost the same resistance to mechanical, chemical and / or environmental influences as decorated molded parts with insert sheets having solvent-based decoration.
[0009] Layers, plies and films are understood in particular to mean essentially planar, and therefore monolayer or multilayer structures. Films are preferably self-supporting. Layers or plies can be, for example, self-supporting or non-self-supporting.
[0010] Advantageous embodiments of the invention are set forth in the dependent claims.
[0011] Preferably, the substrate may comprise a material or a combination of materials selected from ABS, PC, PPA, POM, PMMA, PP, individually or in combination, as a laminate, coextrusion or mixture. ABS (= acrylonitrile butadiene styrene copolymer) is preferably used as the material of the insert sheet, because these plastic substrates are easy to process, easy to decorate using wet varnish systems, and have good resistance to environmental influences. In some embodiments, other materials can also be used for the substrate. In general, it is useful to use a material similar to the plastic compound used to back-inject the insert sheet. The similarity of the substrate material and the plastic compound improves the adhesion between these two elements.
[0012] The substrate may also have a layer thickness of 200 μm to 750 μm, preferably 350 μm to 500 μm.
[0013] Additionally, the water-based adhesive layer may be directly adjacent to the surface of the substrate. The main challenge of the water-based adhesive layer is to provide a good adhesion between the transfer ply and the substrate. As will be explained later for the decorated molded part, a number of requirements must be met depending on the resistivity. The adhesion of the decorative transfer ply to the substrate is one of them.
[0014] Additionally, to transfer the transfer ply of the transfer film by thermal lamination, the adhesive layer may be activated and then cured to form a secure bond to the substrate. Preferably, the curing of the water-based adhesive layer occurs after the insert sheet is formed or deep drawn.
[0015] The transfer film itself, which is used to decorate the insert sheet by transferring the transfer ply by thermal lamination, includes a carrier layer as described above.
[0016] It is preferred that the carrier layer of the transfer film contains PET as a material and has a layer thickness of 6 μm to 100 μm.
[0017] It is also preferable that the carrier layer is peeled off after the transfer ply is transferred to the base material of the insert sheet.
[0018] For this reason, the transfer film may also include a release layer, especially a water-based topcoat layer, preferably disposed between the carrier layer and the transfer ply.
[0019] The release layer may also be an aqueous release layer. The aqueous release layer has in particular a layer thickness of 0.01 μm to 1 μm, preferably 0.05 μm to 0.3 μm. Furthermore, it is possible for the aqueous release layer to comprise one or more aqueous compounds, preferably one or more polymers and / or oligomers. Such polymers and / or oligomers are preferably selected from polyvinyl alcohol, polyvinylpyrrolidone, carboxymethylcellulose, methylcellulose, polyols, starch, sugars, gum arabic, gelatin, lipids, polyethylene oxide, polyvinyl butyral, polyesters, polyurethanes, polyacrylic acid and / or polyamides. It is possible for the aqueous release layer to comprise a combination of these polymers and / or oligomers. The aqueous release layer preferably comprises polyvinyl alcohol, in particular polyvinyl alcohol made from partially saponified polyvinyl acetate with a degree of saponification of 75% to 100%.
[0020] Alternatively, the release layer may not be water-based.Preferably, the release layer comprises at least one material or combination of materials selected from wax, carnauba wax, Montan acid ester, polyethylene wax, polyamide wax, PTFE wax, silicone, melamine formaldehyde resin.In an advantageous embodiment, at least one release layer can have a layer thickness of less than 1 μm, in particular less than 0.5 μm.
[0021] The release layer is preferably a polymer release layer that has better and / or different release behavior than conventional carrier layers. Such a release layer is irreversibly bonded to the carrier layer, and the transfer ply is placed on the release layer. The transfer ply can be more easily peeled off from the carrier layer, particularly with the polymer release layer, so that a higher quality decoration of the insert sheet is achieved.
[0022] As mentioned above, the transfer ply includes, inter alia, an aqueous topcoat layer, at least one aqueous color layer, and an aqueous adhesive layer, disposed on the carrier layer in the following order: In some embodiments, the transfer film may include an aqueous tie coat layer, preferably disposed between the aqueous topcoat layer and the at least one aqueous color layer. The tie coat layer may further improve and stabilize the adhesion between the aqueous topcoat layer and the aqueous color layer.
[0023] The aqueous tie coat layer may have a layer thickness of 0.5 μm to 20 μm, preferably 1 μm to 15 μm, and more preferably 1.5 μm to 7 μm.
[0024] The aqueous tie coat layer may comprise 20% to 50% by weight of an aqueous acrylic or polyester or polyurethane binder, 50% to 80% by weight of deionized water, 0.1% to 5% by weight of a leveling agent, and 0.1% to 5% by weight of an antifoaming agent. This composition provides improved printability, especially for gravure printing.
[0025] Additionally, the aqueous tie coat layer may be applied onto the surface of the carrier layer, preferably onto the surface of the aqueous top coat layer, by gravure printing.
[0026] Preferably, during application of the aqueous tie coat layer, the aqueous tie coat layer has a kinetic viscosity of 0.10 Pa·s to 1.0 Pa·s, preferably 0.2 Pa·s to 0.8 Pa·s, more preferably 0.3 Pa·s to 0.5 Pa·s.
[0027] Furthermore, it is preferred that the aqueous topcoat layer has a layer thickness of 2 μm to 100 μm, preferably 5 μm to 80 μm, more preferably 15 μm to 50 μm. The selection of such a layer thickness provides corresponding protection on the one hand and further processability of the transfer film on the other hand, ensuring that delamination does not occur at the interface between the aqueous topcoat layer and the other layers of the transfer ply. Furthermore, this improves the resistance of the insert sheet, in particular the decorated injection molded part, to mechanical and / or physical and / or chemical environmental influences, since the aqueous topcoat layer can represent the outer layer of the insert sheet and / or the decorated injection molded part.
[0028] The aqueous topcoat layer may also contain 10% to 40% by weight of an aqueous acrylic binder or an aqueous polyurethane binder, 50% to 80% by weight of deionized water, 0.1% to 5% by weight of a leveling agent, and 0.2% to 3% by weight of an antifoaming agent. This composition provides improved printability, especially for slot dies.
[0029] More preferably, the aqueous topcoat layer is applied to the surface of the carrier layer by a slot die.
[0030] Furthermore, during application of the aqueous topcoat layer, the aqueous topcoat layer has a kinetic viscosity of 0.10 Pa·s to 1.0 Pa·s, preferably 0.2 Pa·s to 0.8 Pa·s, and more preferably 0.3 Pa·s to 0.5 Pa·s.
[0031] The at least one aqueous color layer may be formed as a single or multi-layer aqueous color layer. This aqueous color layer preferably comprises one or more layers. The at least one aqueous color layer preferably has a layer thickness of 0.5 μm to 20 μm, preferably 1 μm to 15 μm, more preferably 1.5 μm to 7 μm. The at least one aqueous color layer may preferably have one or more aqueous color layers, in particular pigmented varnish layers. These aqueous color layers can in each case be dyed differently and / or formed transparent and / or opaque and can also be separated by one or more further layers, in particular transparent layers. The aqueous color layers can in each case be present over the entire surface of their layer plane or only partially within their layer plane. The aqueous color layers are preferably applied by known printing methods selected from gravure printing, screen printing, offset printing, inkjet printing, pad printing, xerographic printing or combinations thereof. The aqueous color layer may be composed of binders and colorants and / or fillers and / or pigments, in particular also optically variable pigments and / or interference layer pigments and / or liquid crystal pigments and / or magnetically orientable pigments and / or thermochromic pigments and / or metallic pigments. Furthermore, the aqueous color layer may also contain phosphorescent and / or luminescent dyes. The colorants may include color dyes and / or color pigments.
[0032] In the present context, transparent means in particular a region within the wavelength range of light visible to a human observer, in particular from 380 nm to 780 nm, in which the transmittance averaged over this wavelength range is greater than 50%, preferably greater than 70%, particularly preferably greater than 80%.
[0033] In the present context, opaque means in particular a region within the wavelength range of light visible to a human observer, in particular between 380 nm and 780 nm, in which the transmittance averaged over this wavelength range is less than 40%, preferably less than 30%, particularly preferably less than 20%.
[0034] Furthermore, it is preferred that at least one aqueous color layer is made to take on the decorative aspect of the transfer film, especially the insert sheet. At least one aqueous color layer may be arranged with a pattern. By "patterned" it is preferably meant having one or more patterns. The patterns are in particular graphically designed contours, graphic representations, images, symbols, logos, endless patterns, portraits, alphanumeric characters, text, gridding, etc., or a combination of one or more of the above patterns.
[0035] More preferably, the or each water-based colour layer has a registration tolerance of -0.25mm to +0.25mm.
[0036] By registration (position) or registration (alignment), or registration accuracy (positional precision) or registration accuracy (alignment precision), is meant the positional precision of two or more elements and / or layers relative to one another. Registration precision is what varies within predefined tolerances that are as small as possible. At the same time, the registration precision of several elements and / or layers relative to one another is an important feature to increase the reliability of the process. Positionally accurate positioning can be influenced in particular by perceptual, preferably optically detectable registration (alignment) marks or register marks. These registration (alignment) marks or register marks can represent specific separate elements or regions or layers or can themselves be part of the element or region or layer to be positioned.
[0037] At least one aqueous color layer may comprise 20% to 40% by weight of an aqueous acrylic, polyester or polyurethane binder, 60% to 80% by weight of deionized water, 5% to 20% by weight of at least one color pigment, 0.5% to 20% by weight of a dispersing additive, 0.1% to 5% by weight of a leveling agent, and 0.1% to 5% by weight of an antifoaming agent. This composition provides improved printability, especially for gravure printing.
[0038] Additionally, at least one aqueous color layer can be applied by gravure printing onto the surface of the carrier layer, preferably on top of the aqueous topcoat layer or on top of the aqueous tie coat layer.
[0039] Furthermore, during the coating of the at least one aqueous color layer, the at least one aqueous color layer may have a kinetic viscosity of 0.10 Pa·s to 1.0 Pa·s, preferably 0.2 Pa·s to 0.8 Pa·s, more preferably 0.3 Pa·s to 0.5 Pa·s, such a viscosity improves the printability of the at least one aqueous color layer.
[0040] It can also be advantageous if at least one aqueous adhesive layer has a layer thickness of 0.5 μm to 20 μm, preferably of 1 μm to 15 μm and more preferably of 1.5 μm to 7 μm.
[0041] Furthermore, at least one water-based adhesive layer may comprise 20% to 50% by weight of a water-based acrylic or polyester or polyurethane binder, 50% to 80% by weight of deionized water, 0.1% to 5% by weight of a leveling agent, and 0.1% to 5% by weight of an antifoaming agent. This composition provides improved printability, especially for gravure printing.
[0042] The aqueous adhesive layer may also be applied onto the surface of the carrier layer, preferably onto the surface of at least one aqueous color layer, by gravure printing.
[0043] Furthermore, during application of the aqueous adhesive layer, it is preferred that the aqueous adhesive layer has a dynamic viscosity of 0.10 Pa·s to 1.0 Pa·s, preferably 0.2 Pa·s to 0.8 Pa·s, and more preferably 0.3 Pa·s to 0.5 Pa·s.
[0044] Furthermore, the aqueous topcoat layer and / or the aqueous tie coat layer and / or the at least one aqueous color layer and / or the aqueous adhesive layer may be applied at a printing speed of 5 m / min to 200 m / min, preferably 10 m / min to 100 m / min, more preferably 15 m / min to 100 m / min. Preferably, such printing speed can be achieved based on the above composition and viscosity. Such high printing speed increases the throughput and therefore the efficiency.
[0045] After applying the layer of transfer ply, it is preferred to dry the layer, preferably the aqueous topcoat layer and / or the aqueous tie coat layer and / or the at least one aqueous color layer and / or the aqueous adhesive layer at a drying temperature of 80° C. to 200° C., preferably 90° C. to 180° C., more preferably 100° C. to 150° C. Drying the layers ensures that the layers have sufficient adhesion to each other.
[0046] After the layers have dried, the transfer foil is produced as an intermediate product for the insert sheet. Depending on the application, the insert sheet can be produced on the customer's premises or immediately downstream of the transfer film production.
[0047] As described above, in order to preferably produce the insert sheet, the transfer ply of the transfer film is transferred to the base material of the insert sheet by thermal lamination. The thermal lamination is preferably performed at a lamination speed of 0.2 m / min to 60 m / min, preferably 0.5 m / min to 40 m / min, and more preferably 1 m / min to 20 m / min.
[0048] Furthermore, the thermal lamination may be carried out at a lamination temperature of 90°C to 180°C, preferably 80°C to 160°C, and more preferably 100°C to 150°C.
[0049] Also, the thermal lamination may be carried out at a lamination pressure of 5 bar to 100 bar, preferably 10 bar to 90 bar, and more preferably 20 bar to 60 bar.
[0050] During the thermal lamination, the layer of the transfer ply can lose toughness due to heat exposure and thus become deformable and flexible. This is advantageous for the subsequent molding or deep drawing of the insert sheet. The layer of the transfer sheet can then withstand sometimes violent stretching and compression without cracking or wrinkling. As a result, a high-quality and uniform decoration on the insert sheet is obtained. However, the method of the present invention may further comprise a step of curing the transfer ply, preferably the water-based topcoat layer and / or the water-based tie-coat layer and / or at least one water-based color layer and / or the water-based adhesive layer, preferably after forming or deep drawing of the green body or the insert sheet, by UV irradiation.
[0051] Curing ensures that the layers have sufficient adhesion to each other and are resistant to the effects of the external environment.
[0052] Additionally, the method of the present invention may further comprise the step of peeling off the carrier layer.
[0053] Preferably, the carrier layer is peeled off before the insert sheet is deep drawn or formed or after the insert sheet is deep drawn or formed.
[0054] As mentioned at the beginning, the automotive industry places high requirements on decorated injection-molded parts, for example for interior parts. It is therefore preferable that the insert sheet or the decorated injection-molded part meets these requirements. This is preferably demonstrated by suitable tests as described below.
[0055] Injection-molded parts decorated with the insert sheet according to the invention were used in all subsequent tests. This means that all layers of the insert sheet are in the cured state. However, it is also possible to use only non-back-injected insert sheets for the tests. However, it was decided to carry out the tests on properly decorated injection-molded parts, because they are easier to handle.
[0056] As mentioned at the beginning, VOCs (= volatile organic compounds) should be reduced or avoided in transfer films and / or insert sheets and / or decorative molded parts.
[0057] To measure VOCs, a Thermo Fisher GC-MS system is used, consisting of a gas chromatograph equipped with an FID detector (Flame Ionization Detector) or a mass spectrometer, such as an ISQ QD&Trace 1300 GC with a Combi PAL autosampler. Furthermore, the gas chromatograph is equipped with a wall-coated open tubular (WCOT), such as Zebron ZB-WAX, with a length of 30 m, an inner diameter of 0.25 mm and a film thickness of 0.25 μm.
[0058] A sample of the insert sheet and / or transfer film is divided into pieces weighing greater than 10 mg and less than 25 mg. It is recommended to use an analytical balance, preferably with an accuracy of at least 0.1 mg. These pieces are weighed to 2.000 g ± 0.001 g and placed into a headspace vial of 20 ml volume. For each sample, three headspace vials should be prepared and measured.
[0059] Prior to the measurement, the headspace vial containing the sample is conditioned into a headspace sampling vial in a gas chromatography oven at a temperature of 120°C for 5 hours ± 5 minutes in order to enrich the vial with substances contained in the sample. The vial must be analyzed immediately after this. At least three samples must be analyzed. It must be ensured that the application volumes are identical and reproducible for all sample analyses, blank vials and calibration solutions.
[0060] The samples are measured under the following test conditions: First, a constant temperature of 50 °C is maintained for 3 minutes in the gas chromatography mass spectrometry furnace. Such a furnace is an oven for conditioning the samples. Then the temperature is heated to 200 °C at a rate of 12 °C / min. Once the temperature of 200 °C is reached, the temperature is maintained for 4 minutes. The injection port temperature is 200 °C and the detector temperature is 250 °C. The split ratio is about 1:20. As carrier gases, helium and nitrogen are used with gas velocities of 22 cm / s to 27 cm / s. The carrier gases are injected separately and a mixture in the furnace is determined.
[0061] External standard calibration profiles are created for quantitative measurement of total carbon emissions and for measurement of the amounts of specific individual substances.
[0062] Acetone serves as a calibrator for total carbon emissions, and for each individual substance, the substance itself needs to be used.
[0063] A general calibration with seven calibration solutions must be performed both after the installation of a new column in the gas chromatography furnace and after each modification of this equipment. In addition, check calibrations must be performed with at least three solutions at least every four weeks.
[0064] The preparation of the calibration solutions is made with acetone and n-butanol. The seven calibration solutions preferably have concentrations of 0.1g, 0.5g, 1g, 5g, 10g, 50g, 100g of acetone per liter in n-butanol as the calibration sample. At least three solutions with 0.5g, 5g, and 50g of acetone per liter need to be used for the check calibration. Before the check calibration, it is necessary to ensure that no peaks occur simultaneously for n-butanol and acetone.
[0065] All materials used during calibration should be of at least reagent grade quality.
[0066] During the calibration run, a 10 μl syringe is used to take 4 μl ± 0.2 μl of solution (from the lowest concentration) and inject it into an empty 20 ml headspace vial, which is immediately sealed with polytetrafluoroethylene. Note that there should be no air bubbles in the syringe and that each calibration solution requires at least three vials.
[0067] The vials containing the calibration solutions are then subjected to a temperature treatment at a constant temperature of 120°C for a duration of 1 hour. The calibrated samples are then analyzed by mass spectrometry and recorded by a computer. Each sample produces a respective peak in the spectrum. Each peak has a specific width and a specific height, which together define the peak area of each calibrated sample. The area values from each peak area from the calibration solutions are then plotted on a second diagram with the peak area on one axis (Y) and the different acetone concentrations from the calibration solutions on the other axis (X).
[0068] A straight line is then plotted on this second diagram of the acetone peak area versus the concentration of the calibration solution (in g / l). This plotted ideal line defines the calibration curve. Furthermore, during the computer analysis, the correlation coefficient (R) is automatically obtained, which must be greater than 0.995, otherwise another calibration is required. The slope of the plotted line represents the calibration coefficient k, which represents the total carbon emission, while k(i) represents the emission of each individual substance. The coefficient k has the following units (number 1):
number
[0069] Overall carbon emission value EG (unit: μg C / g サンプル ) is preferably calculated according to the following formula (Equation 2):
number
number
[0070] In particular, the insert sheet, in particular the transfer film or the decorative molded part, preferably has a C / G content of 40 μg C / g, measured according to VW interior spec TL226. サンプル It has been shown to be advantageous to have a carbon emission value EG of: Furthermore, it is preferred that at least three samples are tested.
[0071] The overall emission value Ei (in μg / g) is preferably calculated according to the following formula (Equation 4):
number
[0072] For the odor test, a test piece of the insert sheet is stored in a 1 liter storage glass at 80°C for 2 hours. The test piece has, for example, a length of 18.8 cm and a width of 11 cm. The test piece is then removed and allowed to stand for 5 minutes. The test piece is then tested for odor intensity by three different people independently. A rating is given according to the PV3900 scale as shown below: [Table 1]
[0073] In particular, insert sheets, particularly decorative molded parts, have been shown to advantageously have an odor test result of a level of 2-3 according to the PV3900 scale measured in accordance with VW interior specification TL226.
[0074] For the cream and sun lotion tests, the surfaces of the test specimens, in particular the surfaces of the insert sheets and / or the decorated molded parts, are covered with gauze, and different test specimens are used for the cream and sun lotion tests, respectively. The gauze is preferably cotton gauze (20 count). For each test specimen, the cream or sun lotion is applied onto the gauze and pressed onto the gauze so that the cream or sun lotion fills the gaps of the gauze evenly and completely. For cream and sun lotion, a general test box with several test creams, called Thierry PV 3964, is used. After the cream or sun lotion has been applied, the test specimens with the gauze are placed in an air circulating oven at a temperature of 80±2°C for 24 hours. The gauze is then removed and the surface of the test specimen is washed so that the cream or sun lotion is completely removed.
[0075] The specimen and the original insert sheet, particularly the decorated molded part, are then evaluated by the grayscale test and / or the visual and haptic properties test and / or the cross-cut test and / or the scratch resistance test, as described below. Each of the above tests must be passed to pass the cream and sun lotion test.
[0076] In particular, the insert sheet, particularly the decorative molded part, has been advantageously shown to pass cream and sun lotion tests measured in accordance with VW interior specification TL226.
[0077] For the hydrolysis test, the test specimens, in particular the insert sheets and / or the decorated molded parts, are placed in a hydrolysis test chamber, for example in a high and low temperature humidity heat chamber, in particular in a chamber of type PRO C / 340 / 70 / 3 from Weiss Technik GmbH (35447 Reiskirchen, Germany), and aged at a temperature of 90±2°C and a relative humidity of 95% or more for a duration of 72 hours.
[0078] The specimen and the original insert sheet, particularly the decorated molded part, are then evaluated by the grayscale test and / or the visual and haptic property test and / or the cross-cut test and / or the scratch resistance test, as described below. Each of the above tests must be passed to pass the hydrolysis test.
[0079] In particular, the insert sheet, and in particular the decorative molded part, has been shown to advantageously pass hydrolysis tests measured in accordance with VW interior specification TL226.
[0080] For the lightfastness test, the test specimens, in particular the insert sheets and / or the decorated molded parts, are placed in a xenon lamp weathering test chamber, for example in a "Xenotest Beta+" from Atlas Material Testing Technology GmbH, 63589 Linsengericht-Altenhaslau, Germany. Also in the test chamber, a filter, for example a Xenochrom 320 filter, is placed in the test chamber so that the filter surrounds the test specimen. The black standard temperature is set to 100±3°C and the test specimen room temperature is set to 65±3°C. Furthermore, the relative humidity is set to 20±10%. The test specimens are subjected to a luminescence test of 60 W / m2 measured in the wavelength range of 300 nm to 400 nm for a duration of 320 hours. 2 The radiation intensity is 100 .mu.m.
[0081] The specimen and the original insert sheet, particularly the decorated molded part, are then evaluated by a grayscale test and / or a visual and haptic property test and / or a cross-cut test and / or a scratch resistance test, as described below. Each of the above tests must be passed to pass the lightfastness test.
[0082] In particular, the insert sheet, and in particular the decorative molded part, has been shown to advantageously pass light resistance tests measured in accordance with VW interior specification TL226.
[0083] Furthermore, it is preferred that the insert sheet, in particular the decorated molded part, has a grey scale rating of 4 or more for the cream test and / or the sun lotion test and / or the hydrolysis test and / or the light fastness test measured according to DIN EN 20105-A02. The grey scale test detects changes in colour. For this purpose, the exact colourimetric specification of the scale is given as a permanent record. The essential, or 5-point scale, consists of 5 pairs of colour chips of matte grey, showing a perceived colour difference corresponding to fastness ratings 5, 4, 3, 2 and 1. This essential scale may be augmented by providing similar chips or swatches showing a perceived colour difference corresponding to the half-point fastness ratings of 4-5, 3-4, 2-3 and 1-2, such a scale being called a 9-point scale. In the present case, a 9-point scale was used. The first member of each pair is of neutral grey colour and the second member of the pair, showing fastness rating 5, is identical to the first member. The second members of the remaining pairs become increasingly lighter in color, so that each pair exhibits increasing colorimetrically defined contrast or perceived color difference. Full colorimetric specifications are shown in the table below. [Table 2]
[0084] Further, reference is made to Figure 9 where the grey scale is shown, for example, a rating of 5 is given only if there is no discernible difference between the tested specimen and the original material.
[0085] The test specimens had to be neutral gray in color and were measured with a spectrophotometer including a specular reflectance component. Colorimetric data were calculated using the CIE 1964 supplementary standard color system for illuminant D65.
[0086] A piece of the original insert sheet, in particular a piece of the decorative molded part, is placed side by side in the same plane as the tested specimen and oriented in the same direction. The gray scale is placed nearby in the same plane. A standard illuminant D65 in a light cabinet is arranged to be incident at approximately 45° on the surface. The observation direction is approximately perpendicular to the plane of the surface. The distance between the observer's eye and the test specimen, in particular the insert sheet and / or the decorative molded part, is approximately 50 cm. The difference between the original insert sheet, in particular the decorative molded part, and the tested specimen is evaluated taking into account the gray scale.
[0087] Furthermore, it is preferred that the insert sheet, in particular the decorative molded part, passes visual and property tests for the cream test and / or the sun lotion test and / or the hydrolysis test and / or the light resistance measured in accordance with VW interior specification TL 226. For this purpose, for each of the cream test and / or the sun lotion test and / or the hydrolysis test and / or the light resistance, a visual evaluation is carried out under standard illuminant D65 in a light cabinet at a distance of 50 cm between the observer's eye and the test piece, preferably the insert sheet or the decorative molded part. The test piece is observed under two different angular positions relative to the light source, namely oblique view (see FIG. 7a) and top view (see FIG. 7b). It is shown that no changes occurred in visual appearance or tactile properties compared to the untested test piece. For example, no cracking, foaming, color shift, clouding, delamination, softening or deformation occurred.
[0088] In particular, it has been advantageously shown that during adhesion testing, the adhesion measured on the surface of the test area in accordance with DIN EN ISO 2409:2013-06 is in the range GT0 to GT1 and / or the adhesion measured in accordance with ASTM D 3359-09, preferably test method B, is in the range 5B to 4B, preferably with the aqueous topcoat layer being fully cured.
[0089] The adhesive strength is measured by a cross-cut test, in particular according to DIN EN ISO 2409:2013-06, preferably according to the German version of DIN EN ISO 2409:2013-0 (Beschichtungsstoffe-Gitterschnittpruefung [Paints and varnishes - cross-cut test], publication date 2013-06). In particular, in each case in at least one coating, six cuts are made vertically and six cuts are made horizontally and / or six parallel-running cuts are made at an angle of 90° to six further parallel-running cuts, preferably using a knife, preferably using a stencil. The cuts also penetrate the aqueous topcoat layer, in particular with a depth to the thickness of the transfer ply, and / or are cut into the molded part. The cut width is selected in particular depending on the layer thickness of the aqueous topcoat layer, in particular the thickness of the transfer ply.
[0090] In the case of aqueous topcoat layer thicknesses, in particular transfer ply thicknesses, having a layer thickness of less than 60 μm, the distance between the incisions is preferably about 1 mm.
[0091] In particular, in a top view of the aqueous topcoat layer, an incision is preferably introduced in a measurement area, preferably of square shape, which completely includes the surface of the test area. The measurement area preferably thus includes at least one coating over at least a part of the surface. A transparent adhesive tape or adhesive crepe tape, in particular having an adhesion of 6 N / 25 mm to 10 N / 25 mm, is preferably applied to the surface of the test area. The transparent adhesive tape or adhesive crepe tape is preferably peeled off from the surface, in particular in a period of 0.5 s to 1 s after application, preferably at an angle of 60°.
[0092] The evaluation is carried out in particular by visual evaluation of the surface of the test area and classification into cross-cut characteristic values, preferably abbreviated GT0 to GT5, from 0 (very good adhesive strength) to 5 (very poor adhesive strength).
[0093] Alternatively or additionally, adhesive strength can be measured according to ASTM D 3359-09, test method B.
[0094] The criteria for the classification of the corresponding characteristic values are preferably found in the table below, in particular possible surfaces of the test areas are shown diagrammatically in Figures 8a, 8b, 8c and 8d. [Table 3]
[0095] Therefore, it preferably means that within the range of GT0 to GT1 and / or within the range of 5B to 4B, the peeled off area is at most 5%.
[0096] It is furthermore preferred that the insert sheet, in particular the decorated molded part, has an adhesion test value ISO in the range GT0 to GT1 for the cream test and / or the sunlotion test and / or the hydrolysis test and / or the light fastness measured by cross-cut according to DIN EN ISO 2409:2013-06.
[0097] In particular, the insert sheet, in particular the decorative molded part, has been advantageously shown to pass the scratch resistance test for the cream test and / or the sun lotion test and / or the hydrolysis test and / or the light resistance measured in accordance with the VW interior specification TL226. For the scratch resistance test, an Erichsen hardness test pencil type 318 or type 318S (Erichsen GmbH & Co. KG, Hemer 58675, Germany) with a 10-N load and a Bosch test tip (diameter 0.75 mm) is used. For the cream test and / or the sun lotion test and / or the hydrolysis test and / or the light resistance, respectively, it has been shown that no peeling of the paint surface occurs. Furthermore, the mark of pressing caused by loading the substrate, for example the insert sheet and / or the decorative molded part, is acceptable.
[0098] Furthermore, it is preferred that the insert sheet passes the cream test and / or the sun lotion test and / or the hydrolysis test and / or the light resistance test measured in accordance with VW interior specification TL226.
[0099] The insert sheet according to the present invention has been shown to meet all the requirements of the automotive industry.In addition, the aqueous layer has been proven to have almost the same or even better resistance than the solvent-based layer used in the past.For example, the comparison between the conventional insert sheet with the solvent-based layer and the insert sheet with the aqueous layer of the present invention is shown in the following table. [Table 4]
[0100] As can be seen from the VOC test, the water-based insert sheet reaches a better value. The lower the VOC test value, the better and more environmentally friendly the insert sheet is. Furthermore, for odor test, the water-based insert sheet according to the present invention has a better performance than the conventional insert sheet with solvent-based layer.
[0101] The transfer film according to the invention, the insert sheet according to the invention and the method for producing the insert sheet according to the invention are used, for example, in the automotive sector, in particular for cockpit parts, panels, armatures and the like.
[0102] Further embodiments of the invention are shown in the drawings and described below, and therefore the illustrated embodiments should not be understood as limiting. [Brief description of the drawings]
[0103] [Figure 1] FIG. 2 is a schematic diagram of a transfer film. [Diagram 2] FIG. 2 is a schematic diagram of a transfer film attached to a substrate. [Diagram 3] FIG. 2 is a schematic diagram of an insert sheet. [Figure 4]FIG. 2 is another schematic diagram of a transfer film. [Diagram 5] FIG. 2 is another schematic diagram of a transfer film applied to a substrate. [Figure 6] FIG. 13 is another schematic diagram of the insert sheet. [Figure 7a] FIG. 1 is a schematic diagram of two different observation positions for visual and haptic property testing. [Figure 7b] FIG. 1 is a schematic diagram of two different observation positions for visual and haptic property testing. [Figure 8a] FIG. 1 is a schematic diagram of a test area in a cross-cut test. [Figure 8b] FIG. 1 is a schematic diagram of a test area in a cross-cut test. [Figure 8c] FIG. 1 is a schematic diagram of a test area in a cross-cut test. [Figure 8d] FIG. 1 is a schematic diagram of a test area in a cross-cut test. [Figure 9] FIG. 1 shows the nine-level grayscale used in the grayscale test. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0104] FIG. 1 shows a schematic diagram of a transfer film 1. Such a transfer film 1 is used, for example, to decorate an insert sheet 10 used in the so-called insert molding process. In insert molding, a preformed insert sheet 10 is inserted into an injection mold and an injection molding compound is back-injected to obtain a decorated injection molded part. By using the insert sheet 10, injection molded parts having complex shapes can be decorated.
[0105] The transfer film 1 according to FIG. 1 comprises a carrier layer 2 and a transfer ply 3, the latter comprising a water-based topcoat layer 4, a water-based color layer 5 and a water-based adhesive layer 6 arranged on the carrier layer 2 in the following order. Such a transfer ply 3 comprising only water-based layers offers the great advantage of avoiding harmful or unhealthy solvents. Generally, when solvent-containing layers are used, the solvent or volatile organic compounds can diffuse through the layer and thus enter, for example, the ambient air to be inhaled by a person. Water-based coatings are therefore more environmentally harmless and healthier than solvent-based coatings.
[0106] Preferably, the carrier layer 2 comprises PET as a material and has a layer thickness of 3 μm to 300 μm.
[0107] Advantageously, the aqueous topcoat layer 4 has a layer thickness of 2 μm to 100 μm, preferably 5 μm to 80 μm, and more preferably 15 μm to 50 μm. The aqueous topcoat layer 4 functions as a kind of protective layer for the underlying decorative layer such as the aqueous color layer 5. After the transfer ply 3 of the transfer film 1 is applied to the insert sheet 10 and the carrier layer 2 is removed, the aqueous topcoat layer 4 corresponds to the outermost layer of the layer structure. Preferably, the aqueous topcoat layer 4 has a certain resistance to mechanical and / or chemical and / or physical environmental influences.
[0108] Preferably, the aqueous topcoat layer 4 contains 10% to 40% by weight of an aqueous acrylic binder or an aqueous polyurethane binder, 50% to 80% by weight of deionized water, 0.1% to 5% by weight of a leveling agent, and 0.2% to 3% by weight of an antifoaming agent.
[0109] Advantageously, the aqueous topcoat layer 4 is applied onto the surface of the carrier layer 2 by means of a slot die. Thus, during the manufacturing process of the transfer film 1, in particular the insert sheet 10, the carrier layer 2 is preferably provided first, and then the aqueous topcoat layer 4 is printed onto the surface of the carrier layer 2.
[0110] During application of the aqueous topcoat layer 4, the aqueous topcoat layer 4 may have a kinetic viscosity of 0.10 Pa·s to 1.0 Pa·s, preferably 0.2 Pa·s to 0.8 Pa·s, and more preferably 0.3 Pa·s to 0.5 Pa·s.
[0111] Then, in the manufacturing process of the transfer film 1, in particular the insert sheet 10, at least one aqueous color layer 5 may be applied by gravure printing onto the surface of the carrier layer 2, preferably on top of the aqueous topcoat layer 4. Only one aqueous color layer 5 may be applied, or multiple aqueous color layers 5 may be applied.
[0112] Furthermore, during the coating of the at least one aqueous color layer 5, it is preferable that the at least one aqueous color layer 5 has a kinetic viscosity of 0.10 Pa·s to 1.0 Pa·s, preferably 0.2 Pa·s to 0.8 Pa·s, and more preferably 0.3 Pa·s to 0.5 Pa·s.
[0113] In particular, the at least one aqueous color layer 5 comprises 20% to 40% by weight of an aqueous acrylic, polyester or polyurethane binder, 60% to 80% by weight of deionized water, 5% to 20% by weight of at least one color pigment, 0.5% to 20% by weight of a dispersing additive, 0.1% to 5% by weight of a leveling agent, and 0.1% to 5% by weight of an antifoaming agent.
[0114] Furthermore, it is more preferred that the at least one water-based color layer 5 has a register tolerance of -0.25mm to +0.25mm.
[0115] Preferably, the water-based adhesive layer 6 is applied after the at least one water-based color layer 5. For example, the water-based adhesive layer 6 is applied onto the surface of the carrier layer 2, preferably onto the surface of the at least one water-based color layer 5, by gravure printing.
[0116] Advantageously, during application of the aqueous adhesive layer 6, the aqueous adhesive layer 6 has a dynamic viscosity of 0.10 Pa·s to 1.0 Pa·s, preferably 0.2 Pa·s to 0.8 Pa·s, and even more preferably 0.3 Pa·s to 0.5 Pa·s.
[0117] Furthermore, the at least one aqueous color layer 5 has a layer thickness of 0.5 μm to 20 μm, preferably 1 μm to 15 μm, and more preferably 1.5 μm to 7 μm.
[0118] Preferably, at least one water-based adhesive layer 6 contains 20% to 50% by weight of a water-based acrylic, polyester or polyurethane binder, 50% to 80% by weight of deionized water, 0.1% to 5% by weight of a leveling agent, and 0.1% to 5% by weight of an antifoaming agent.
[0119] 2 shows a schematic diagram of the transfer film 1 applied to a substrate 11. For this purpose, the substrate 11 may first be provided, and then the transfer ply 3 of the transfer film 1 may be heat laminated onto the surface of the substrate 11, in particular with the water-based adhesive layer 6 directly adjacent to the surface of the substrate 11.
[0120] Preferably, the thermal lamination is carried out at a lamination speed of 0.2 m / min to 60 m / min, preferably 0.5 m / min to 40 m / min, and more preferably 1 m / min to 20 m / min.
[0121] In particular, the thermal lamination is carried out at a lamination temperature of 90°C to 180°C, preferably 80°C to 160°C, and more preferably 100°C to 150°C.
[0122] Furthermore, it is preferred that the thermal lamination is carried out at a lamination pressure of 5 bar to 100 bar, preferably 10 bar to 90 bar, and more preferably 20 bar to 60 bar.
[0123] Figure 3 shows a schematic diagram of an insert sheet 10. The insert sheet 10 is preferably a laminate of a substrate 11 and a transfer ply 3 of a transfer film 1. In contrast to the illustration shown in Figure 2, the insert sheet 10 no longer has a carrier layer 2. Preferably, the method of the invention further comprises a step of peeling off the carrier layer 2.
[0124] It is further preferred that the substrate 11 comprises a material or a combination of materials selected from ABS, PC, PPA, POM, PMMA, PP, either individually or in combination, as a laminate, coextrusion or blend. In principle, the insert sheet 10 is formed and then the plastic compound is back-injected in an injection mold. Preferably, the substrate 11 of the insert sheet 10 is formed of the same material as the plastic compound.
[0125] In particular, the substrate 11 has a layer thickness of 200 μm to 750 μm, preferably 350 μm to 500 μm. Such a layer thickness ensures that the insert sheet 10 has sufficient stability, especially against high pressures in an injection mold, and is also sufficiently flexible to allow the insert sheet 10 to be shaped before back injection.
[0126] For the application of such insert sheets 10 for decorative purposes in the automotive industry, such as for example cockpit covers, numerous requirements have to be met. These relate, for example, to mechanical, physical and chemical resistance as well as visual appearance.
[0127] For example, the insert sheet 10 has a thermal conductivity of 40 μg C / g, preferably measured in accordance with VW interior spec TL226. サンプルThe carbon emission value EG of the insert sheet 10 is set to 0.05 to 0.05. This means that most VOCs cannot diffuse through the layer of the insert sheet 10. On the one hand, this is due to the fact that the layer of the insert sheet 10 is water-based and therefore does not contain solvents that are usually VOCs. Secondly, this is because the water-based topcoat layer 4 has a high resistance to diffusion, which results in the inhibition of the diffusion of VOCs. The less solvent diffuses through the insert sheet 10 or the layer of the insert sheet 10, the better it is for the environment and for the health of the driver.
[0128] Additionally, it is preferred that the insert sheet 10 have an odor test result of a level of 2-3 according to the PV3900 scale measured in accordance with VW interior specification TL226. As mentioned above, in the odor test, three testers subjectively test the odor of the insert sheet 10 for intensity and rate it on a scale of 1-6, with 1 being undetectable and 6 being intolerable.
[0129] Preferably, the insert sheet 10 passes the cream test and / or the sun lotion test and / or the hydrolysis test and / or the light resistance test measured according to VW interior specification TL 226. To pass each test listed above, for each test, samples are tested for gray scale, optical appearance, adhesion and scratch resistance.
[0130] In particular, the insert sheet 10 has a grey scale rating of 4 or higher for the cream test and / or the sunlotion test and / or the hydrolysis test and / or the lightfastness test measured in accordance with DIN EN 20105-A02.
[0131] Additionally, it is preferred that the insert sheet 10 passes visual and property tests for cream test and / or sun lotion test and / or hydrolysis test and / or light resistance measured in accordance with VW interior specification TL226.
[0132] It is further preferred that the insert sheet 10 has an adhesion test value ISO in the range GT0 to GT1 for the cream test and / or the sunlotion test and / or the hydrolysis test and / or the light fastness measured by cross-cut in accordance with DIN EN ISO 2409:2013-06.
[0133] Preferably, the insert sheet 10 passes the scratch resistance test for cream test and / or sun lotion test and / or hydrolysis test and / or light fastness test measured in accordance with VW interior specification TL226.
[0134] FIG. 4 shows an alternative embodiment of a transfer film 1 which essentially corresponds to the structure of the transfer film 1 according to FIG. 1, with the difference that the transfer film 1 comprises an aqueous tie coat layer 7 arranged between the aqueous top coat layer 4 and at least one aqueous color layer 5.
[0135] The aqueous tie-coat layer 7 preferably has a layer thickness of 0.5 μm to 20 μm, preferably 1 μm to 15 μm, and more preferably 1.5 μm to 7 μm.
[0136] In particular, the aqueous tie coat layer 7 contains 20% to 50% by weight of an aqueous acrylic, polyester, or polyurethane binder, 50% to 80% by weight of deionized water, 0.1% to 5% by weight of a leveling agent, and 0.1% to 5% by weight of an antifoaming agent.
[0137] Preferably, during the production of the transfer film 1, in particular the insert sheet 10, the aqueous tie-coat layer 7 is applied onto the surface of the carrier layer 2, preferably onto the surface of the aqueous top-coat layer 4, by gravure printing.
[0138] Further, preferably, during application of the aqueous tie-coat layer 7, the aqueous tie-coat layer 7 has a kinetic viscosity of 0.10 Pa·s to 1.0 Pa·s, preferably 0.2 Pa·s to 0.8 Pa·s, and more preferably 0.3 Pa·s to 0.5 Pa·s.
[0139] It is further preferred that the aqueous top coat layer 4 and / or the aqueous tie coat layer 7 and / or the at least one aqueous color layer 5 and / or the aqueous adhesive layer 6 are applied at a printing speed of 5 m / min to 200 m / min, preferably 10 m / min to 100 m / min, and more preferably 15 m / min to 100 m / min.
[0140] It may also be possible for the aqueous top coat layer 4 and / or the aqueous tie coat layer 7 and / or at least one aqueous color layer 5 and / or the aqueous adhesive layer 6 to be dried at a drying temperature of 80°C to 200°C, preferably 90°C to 180°C, and more preferably 100°C to 150°C.
[0141] Figure 5 shows another schematic view of a transfer film 1 applied to a substrate 11. In Figure 5, the transfer film 1 described with respect to Figure 4 is applied to a substrate 11. After application of the transfer film 1, in particular the transfer ply 3, to the substrate 11, the method of the invention preferably comprises a step of curing the transfer ply 3, preferably the water-based topcoat layer 4 and / or the water-based tie-coat layer 7 and / or at least one water-based color layer 5 and / or the water-based adhesive layer 6, by UV irradiation, preferably after forming or deep drawing of the substrate or insert sheet.
[0142] Before the transfer film 1 is applied to the substrate 11, the layer of the transfer ply 3 is in an uncured or pre-cured state. This is characterized by the fact that the layer has a sufficiently high viscosity so that it cannot flow but is still deformable. The deformation ability of the individual layers is therefore important, since the insert sheet 10 is subsequently formed and in order to avoid cracks in the decoration, and in particular in the transfer ply 3, during formation. Preferably, the insert sheet 10 or the transfer ply 3 is cured after forming.
[0143] FIG. 6 shows an alternative embodiment of the insert sheet 10 which essentially corresponds to the structure of the insert sheet 10 according to FIG. 3, with the difference that the insert sheet 10 includes an aqueous tie coat layer 7 arranged between the aqueous top coat layer 4 and at least one aqueous color layer 5.
[0144] FIG. 7 shows a schematic diagram of two different observation positions for the visual and haptic property tests described above.
[0145] 8a-d show schematic diagrams of the test area in the cross-cut test, which has been described in detail above.
[0146] Figure 8a shows the surface corresponding to ISO characteristic value GT1 and ASTM characteristic value 4B. As can be seen, small flakes of paint have peeled off at the intersections of the grid lines. The peeled off area is about 5% of the section.
[0147] Figure 8b shows the surface corresponding to ISO characteristic value GT2 and ASTM characteristic value 3B. As can be seen, the paint has flaked off along the edges of the cuts and / or at the intersections of the grid lines. The flaked area is about 15% of the section.
[0148] Figure 8c shows the surface corresponding to ISO characteristic value GT3 and ASTM characteristic value 2B. As can be seen, the coating has partially or completely peeled off in broad strips along the edges of the cuts and / or the coating has completely or partially peeled off in individual sections. The peeled area is about 35% of the section.
[0149] Figure 8d shows the surface corresponding to ISO characteristic value GT4 and ASTM characteristic value 1B. As can be seen, the coating has peeled off in broad strips along the edges of the cuts and / or has completely or partially peeled off on individual sections. The peeled area covers about 65% of the section.
[0150] FIG. 9 shows the nine-level grayscale used in the grayscale test described above. [Explanation of symbols]
[0151] 1 Transfer film 2. Carrier Layer 3 Transfer ply 4. Water-based topcoat layer 5 Water-based color layer 6 Water-based adhesive layer 7 Water-based tie coat layer 10 Insert Sheet 11 Base
Claims
1. An insert sheet (10) comprising a substrate (11) and a transfer ply (3) of a transfer film (1) attached to the substrate (11), The transfer ply (3) comprises at least one water-based adhesive layer (6), at least one water-based color layer (5), and a water-based topcoat layer (4), which are arranged on the substrate (11) in the following order: An insert sheet (10) comprising:
2. The substrate (11) comprises a material or combination of materials selected from ABS, PC, PPA, POM, PMMA, PP, individually or in combination, as a laminate, coextrusion or blend; and / or 2. The insert sheet (10) according to claim 1, characterized in that the substrate (11) has a layer thickness of 200 μm to 750 μm, preferably 350 μm to 500 μm.
3. said water-based adhesive layer (6) being directly adjacent to the surface of said substrate (11); and / or The aqueous top coat layer (4) has a layer thickness of 2 μm to 100 μm, preferably 5 μm to 80 μm, more preferably 15 μm to 50 μm, and / or The aqueous top coat layer (4) is The insert sheet (10) according to claim 1 or 2, characterized in that it contains 10% to 40% by weight of an aqueous acrylic binder or an aqueous polyurethane binder, 50% to 80% by weight of deionized water, 0.1% to 5% by weight of a leveling agent, and 0.2% to 3% by weight of an antifoaming agent.
4. The insert sheet (10) preferably comprises a water-based tie coat layer (7) arranged between the water-based top coat layer (4) and the at least one water-based color layer (5); and / or the aqueous tie coat layer (7) has a layer thickness of 0.5 μm to 20 μm, preferably 1 μm to 15 μm, more preferably 1.5 μm to 7 μm; and / or The insert sheet (10) according to claim 1, characterized in that the water-based tie-coat layer (7) comprises 20% to 50% by weight of a water-based acrylic, water-based polyester, or water-based polyurethane binder, 50% to 80% by weight of deionized water, 0.1% to 5% by weight of a leveling agent, and 0.1% to 5% by weight of an antifoaming agent.
5. the at least one aqueous colour layer (5) has a layer thickness of 0.5 μm to 20 μm, preferably 1 μm to 15 μm, more preferably 1.5 μm to 7 μm; and / or The insert sheet (10) according to claim 1, characterized in that the at least one water-based color layer (5) comprises 20% to 40% by weight of a water-based acrylic, polyester or polyurethane binder, 60% to 80% by weight of deionized water, 5% to 20% by weight of at least one color pigment, 0.5% to 20% by weight of a dispersing additive, 0.1% to 5% by weight of a leveling agent, and 0.1% to 5% by weight of an antifoaming agent.
6. the at least one water-based adhesive layer (6) has a layer thickness of 0.5 μm to 20 μm, preferably 1 μm to 15 μm, more preferably 1.5 μm to 7 μm; and / or The insert sheet (10) according to claim 1, characterized in that the at least one water-based adhesive layer (6) comprises 20% to 50% by weight of a water-based acrylic, water-based polyester, or water-based polyurethane binder, 50% to 80% by weight of deionized water, 0.1% to 5% by weight of a leveling agent, and 0.1% to 5% by weight of an antifoaming agent.
7. The insert sheet (10) preferably has a C / g resistance of 40 μg C / g measured in accordance with VW interior specification TL226. サンプル and / or has a carbon emission value EG of The insert sheet (10) has an odor test result of 2 to 3 according to the PV3900 scale measured in accordance with VW interior specification TL226, and / or The insert sheet (10) according to claim 1, characterized in that the insert sheet (10) has passed a cream test and / or a sun lotion test and / or a hydrolysis test and / or a light resistance test measured in accordance with VW interior specification TL226.
8. said insert sheet (10) has a grey scale rating of 4 or more for said cream test and / or sun lotion test and / or hydrolysis test and / or light fastness test, measured according to DIN EN 20105-A02; and / or The insert sheet (10) has passed the cream test and / or the sun lotion test and / or the hydrolysis test and / or the visual and characteristic test for light resistance measured in accordance with VW interior specification TL 226, and / or said insert sheet (10) has an adhesion test value ISO of GT0 to GT1 for said cream test and / or sun lotion test and / or hydrolysis test and / or light resistance, measured by crosscut according to DIN EN ISO 2409:2013-06, and / or The insert sheet (10) according to claim 1, characterized in that the insert sheet (10) passes the cream test and / or the sun lotion test and / or the hydrolysis test and / or the scratch resistance test for light resistance measured in accordance with VW interior specification TL226.
9. A transfer film (1) for decorating an insert sheet (10), in particular according to any one of claims 1 to 8, A carrier layer (2) and a transfer ply (3), The transfer ply (3) comprises an aqueous topcoat layer (4), at least one aqueous color layer (5) and an aqueous adhesive layer (6) arranged on the carrier layer in the following order:
10. 10. The transfer film (1) according to claim 9, characterized in that the carrier layer (2) comprises PET as material and has a layer thickness of 6 μm to 100 μm.
11. 10. The transfer film (1) according to claim 9, characterized in that the transfer film (1) preferably comprises a release layer, in particular an aqueous topcoat layer (4), arranged between the carrier layer (2) and the transfer ply (3).
12. The aqueous top coat layer (4) has a layer thickness of 2 μm to 100 μm, preferably 5 μm to 80 μm, more preferably 15 μm to 50 μm, and / or The transfer film (1) of claim 9, characterized in that the aqueous topcoat layer (4) comprises 10% to 40% by weight of an aqueous acrylic binder or an aqueous polyurethane binder, 50% to 80% by weight of deionized water, 0.1% to 5% by weight of a leveling agent, and 0.2% to 3% by weight of an antifoaming agent.
13. The transfer film (1) preferably comprises an aqueous tie coat layer (7) disposed between the aqueous top coat layer (4) and the at least one aqueous color layer (5); Preferably, the aqueous tie coat layer (7) has a layer thickness of 0.5 μm to 20 μm, preferably 1 μm to 15 μm, more preferably 1.5 μm to 7 μm, and / or 10. The transfer film (1) of claim 9, characterized in that the water-based tie coat layer (7) comprises 20% to 50% by weight of a water-based acrylic, polyester or polyurethane binder, 50% to 80% by weight of deionized water, 0.1% to 5% by weight of a leveling agent, and 0.1% to 5% by weight of an antifoaming agent.
14. said at least one water-based colour layer (5) having a registration tolerance of -0.25mm to +0.25mm; and / or the at least one aqueous colour layer (5) has a layer thickness of 0.5 μm to 20 μm, preferably 1 μm to 15 μm, more preferably 1.5 μm to 7 μm; and / or 10. The transfer film (1) according to claim 9, characterized in that the at least one aqueous color layer (5) comprises 20% to 40% by weight of an aqueous acrylic or polyester or polyurethane binder, 60% to 80% by weight of deionized water, 5% to 20% by weight of at least one color pigment, 0.5% to 20% by weight of a dispersing additive, 0.1% to 5% by weight of a leveling agent, and 0.1% to 5% by weight of an antifoaming agent.
15. the at least one water-based adhesive layer (6) has a layer thickness of 0.5 μm to 20 μm, preferably 1 μm to 15 μm, more preferably 1.5 μm to 7 μm; and / or 10. The transfer film (1) according to claim 9, characterized in that the at least one water-based adhesive layer (6) comprises 20% to 50% by weight of a water-based acrylic or polyester or polyurethane binder, 50% to 80% by weight of deionized water, 0.1% to 5% by weight of a leveling agent, and 0.1% to 5% by weight of an antifoaming agent.
16. A method for producing an insert sheet (10), preferably an insert sheet (10) according to claims 1 to 8, comprising the steps of: The insert sheet (10) comprises a substrate (11) and a transfer ply (3) of a transfer film (1) according to any one of claims 9 to 15 attached to the substrate (11), providing a carrier layer (2); applying, by printing, an aqueous topcoat layer (4), at least one aqueous color layer (5) and an aqueous adhesive layer (6) on the surface of said carrier layer (2) to provide a transfer film (1), in particular in the following order: Providing a substrate (11); a step of thermally laminating the transfer ply (3) of the transfer film (1) onto the surface of the substrate (11); Including, The method of claim 1, wherein said water-based adhesive layer (6) is directly adjacent to said surface of said substrate (11).
17. The aqueous topcoat layer (4) is applied onto the surface of the carrier layer (2) by a slot die; and / or 17. The method according to claim 16, characterized in that during application of the aqueous top-coat layer (4), the aqueous top-coat layer (4) has a dynamic viscosity of 0.10 Pa.s to 1.0 Pa.s, preferably 0.2 Pa.s to 0.8 Pa.s, more preferably 0.3 Pa.s to 0.5 Pa.s.
18. an aqueous tie coat layer (7) is applied by gravure printing onto the surface of said carrier layer (2), preferably onto the surface of said aqueous top coat layer (4); 17. The method according to claim 16, characterized in that, preferably, during application of the aqueous tie coat layer (7), the aqueous tie coat layer (7) has a dynamic viscosity of 0.10 Pa.s to 1.0 Pa.s, preferably 0.2 Pa.s to 0.8 Pa.s, more preferably 0.3 Pa.s to 0.5 Pa.s.
19. said at least one aqueous color layer (5) is applied by gravure printing onto the surface of said carrier layer (2), preferably on top of said aqueous topcoat layer (4) or said aqueous tie-coat layer (7); and / or 17. The method according to claim 16, characterized in that during application of the at least one aqueous color layer (5), the at least one aqueous color layer (5) has a dynamic viscosity of 0.10 Pa.s to 1.0 Pa.s, preferably 0.2 Pa.s to 0.8 Pa.s, more preferably 0.3 Pa.s to 0.5 Pa.s.
20. said aqueous adhesive layer (6) is applied by gravure printing onto the surface of said carrier layer (2), preferably onto the surface of said at least one aqueous color layer (5); and / or 17. The method according to claim 16, characterized in that during application of the aqueous adhesive layer (6), the aqueous adhesive layer (6) has a dynamic viscosity of 0.10 Pa.s to 1.0 Pa.s, preferably 0.2 Pa.s to 0.8 Pa.s, more preferably 0.3 Pa.s to 0.5 Pa.s.
21. said water-based top-coat layer (4) and / or said water-based tie-coat layer (7) and / or said at least one water-based color layer (5) and / or said water-based adhesive layer (6) are applied at a printing speed of 5 m / min to 200 m / min, preferably 10 m / min to 100 m / min, more preferably 15 m / min to 100 m / min; and / or 17. The method according to claim 16, characterized in that the water-based top-coat layer (4) and / or the water-based tie-coat layer (7) and / or the at least one water-based color layer (5) and / or the water-based adhesive layer (6) are dried at a drying temperature of 80°C to 200°C, preferably 90°C to 180°C, further preferably 100°C to 150°C.
22. the thermal lamination is carried out at a lamination speed of 0.2 m / min to 60 m / min, preferably 0.5 m / min to 40 m / min, more preferably 1 m / min to 20 m / min; and / or The thermal lamination is carried out at a lamination temperature of 90° C. to 180° C., preferably 80° C. to 160° C., more preferably 100° C. to 150° C.; and / or 17. The method according to claim 16, characterized in that the thermal lamination is carried out at a lamination pressure of 5 bar to 100 bar, preferably 10 bar to 90 bar, more preferably 20 bar to 60 bar.
23. curing the transfer ply (3), preferably the water-based topcoat layer (4) and / or the water-based tie-coat layer (7) and / or the at least one water-based color layer (5) and / or the water-based adhesive layer (6) by UV irradiation, preferably after forming or deep drawing of the green body or insert sheet; and / or A step of peeling off the carrier layer (2); 20. The method of claim 16, further comprising: